Exercising Market Power Without Using Prices: Service Time in Online Grocery - Ater, Itai; Shany, Adi (Management Science, 2024)
This paper studies how online grocers use service time to respond to local competition and demand conditions when prices are uniformly set at the national level. Using comprehensive data collected twice a week over three years from 172 Israeli local markets, we show that an online grocer sets identical prices in all markets. By contrast, service time is shorter in more competitive markets and on low-demand days. Next, we exploit regional and temporal variation in entry decisions to examine how the incumbent adjusts its service time when new online grocers enter the market. The incumbent’s service time falls significantly on low-demand days and in monopolistic markets. This decrease begins shortly before entry and is greater when the entrant poses a larger competitive threat. On high-demand days and in competitive markets we do not find a significant change in service time in the months surrounding entry. Our findings suggest that firms use service time to exercise their local market power when prices are unresponsive and that operational considerations affect the extent to which they respond. This paper was accepted by Joshua Gans, business strategy. Funding: Financial support by Eli Hurvitz Institute of Strategic Management, The Henry Crown Institute of Business Research in Israel, The Maurice Falk Institute for Economic Research in Israel Ltd., Coller Foundation, and the Israeli Science Foundation [Grant 568/17] is gratefully acknowledged. Supplemental Material: The online appendices and data files are available at https://doi.org/10.1287/mnsc.2022.01820 .